Le riscritture del mito: il pianto di Briseide e di Andromaca (Prop. 2,8; 2,9; 2,20) - Fedeli, Paolo (Euphrosyne, 2004)
Abstract Going to the elegiac text from the Homeric one, myths have been through a profound modification: so happens for Briseis, who becomes in the elegy a faithful and true mistress of Achilles. Representing Andromacha Propertius contaminates the epic model through the tragic one.